2019
DOI: 10.5001/omj.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Aneurysm of the Internal Carotid Artery as a Complication of Facial Bone Trauma

Abstract: The involvement of the internal carotid artery in dissecting aneurysm is rarely reported in the literature and may occur as a complication of trauma, surgery, and other medical conditions. We report a case of a 22-year-old male who was involved in a motor vehicle accident with associated multiple orthopedic and maxillofacial fractures. During surgical management, the patient was incidentally diagnosed with a dissecting aneurysm involving the right internal carotid artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…9,13 The result of hardware failure is similar to the reported findings of Bergh et al, Parascandolo et al, and Al-Saadi et al 6,21,22 Bleeding has been reported in association with CF and is often related to direct injury or pseudoaneurysm of the internal maxillary artery. 22,23 In this study, bleeding was encountered intraoperatively and was managed immediately by packing and ligation. The two cases of perioperative bleeding found in this study, were reported in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…9,13 The result of hardware failure is similar to the reported findings of Bergh et al, Parascandolo et al, and Al-Saadi et al 6,21,22 Bleeding has been reported in association with CF and is often related to direct injury or pseudoaneurysm of the internal maxillary artery. 22,23 In this study, bleeding was encountered intraoperatively and was managed immediately by packing and ligation. The two cases of perioperative bleeding found in this study, were reported in the literature.…”
Section: Discussionmentioning
confidence: 95%